邻苯二甲酸二乙酯诱导的大鼠尿道下裂与Mafb的表达相关：基于转录组测序结果 (Nan Fang Yi Ke Da Xue Xue Bao, 2019)
OBJECTIVE: To investigate the transcriptome profile of genital tubercles (GTs) in male SD rats and explore the mechanism of hypospadias induced by Di (2-ethylhexyl) phthalate (DEHP). METHODS: Forty time-pregnant SD rats were randomly divided into 4 equal groups, namely GD16 group and GD19 group (in which the male GTs were collected on gestation day[GD]16 and GD19 for RNA-seq, respectively), control group and DEHP exposure group (with administration of oil and 750 mg/kg DEHP by gavage from GD12 to GD19, respectively).In the control and DEHP exposure groups, the GTs were collected from the male fetuses on GD19.5, and scanning electron microscopy and HE staining were used to observe the morphological changes.The differentially expressed genes (DEGs) in the GTs were screened using lllumina HiSeq 2000 followed by GO and KEGG enrichment analyses to characterize the transcriptome profile.Immunofluorescence assay was performed to verify the DEGs (Mafb) identified by RNA-seq results.Immunofluorescence assay and Western blotting were used to examine the expression levels of Mafb in the penile tissue. RESULTS: A total of 1360 DEGs were detected in the GTs between GD16 group and GD19 group by RNA-seq.Among these genes, 797 were up-regulated and 563 were down-regulated.These DEGs were mainly enriched in the cell adhesion plaque signaling pathway, axon guidance signaling pathway, and extracellular matrix receptor signaling pathway.Compared with that in GD16 group, Mafb was significantly up-regulated in GD19 group, which was consistent with the sequencing results.Mafb and β-catenin were significantly down-regulated in DEHP-exposed group compared with the control group (P < 0.01). CONCLUSION: Mafb expression increases progressively with the development of GTs in male SD rats.DEHP exposure causes significant down-regulation of Mafb and β-catenin, suggesting that β-catenin signaling pathway that affects Mafb is related to DEHP-induced hypospadias in SD rats.